Come Back, Amelia Bedelia - I Can Read Book - Level 2 - Peggy Parish (Harper Collins Publisher, 1971)
Amelia Bedelia must look for a new job -- Mrs. Rogers has finally had enough. But for poor Amelia Bedelia, each new job is a bigger mess than the last. Can she ever find a place to belong?
Keywords: Leveled Reader -- Leveled Reader